1995
DOI: 10.1007/bf00298994
|View full text |Cite
|
Sign up to set email alerts
|

Differentiating between orchiectomized rats and controls using measurements of trabecular bone density: A comparison among DXA, Histomorphometry, and peripheral quantitative computerized tomography

Abstract: In studies of rat bone metabolism, trabecular bone density should be measured. Three established methods of measuring trabecular bone include trabecular bone volume by histomorphometry (BV/TV%), trabecular bone density by peripheral quantitative computerized tomography (pQCT), and areal bone density of trabecular-rich regions by dual x-ray absorptiometry (DXA). We compared the ability of these three methods to discriminate between orchiectomized (orchidectomized) rats and controls. Sixteen male Sprague-Dawley … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
43
1

Year Published

1995
1995
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 88 publications
(47 citation statements)
references
References 19 publications
3
43
1
Order By: Relevance
“…Cortical bone was defined by a voxel density greater than or equal to 700 mg/cm 3 , soft tissue by a voxel density of less than or equal to 400 mg/cm 3 , and trabecular bone by a voxel density between 400 and 700 mg/cm 3 . 29,30 The trabecular medullary compartment was defined by the region interior to the endosteal surface of the cortex with a voxel density less than 700 mg/cm 3 .…”
Section: Methodsmentioning
confidence: 99%
“…Cortical bone was defined by a voxel density greater than or equal to 700 mg/cm 3 , soft tissue by a voxel density of less than or equal to 400 mg/cm 3 , and trabecular bone by a voxel density between 400 and 700 mg/cm 3 . 29,30 The trabecular medullary compartment was defined by the region interior to the endosteal surface of the cortex with a voxel density less than 700 mg/cm 3 .…”
Section: Methodsmentioning
confidence: 99%
“…pQCT was performed with the Stratec peripheral quantitative computed tomograph (pQCT) XCT Research M (Norland Corp., Fort Atkinson, WI) specifically modified for use on small bone specimens (software version 5.4B; operating at 70 µm resolution) (Rosen et al 1995, Andersson et al 2002. The machine was calibrated with a standard of hydroxyapatite embedded in acrylic plastic.…”
Section: Peripheral Quantitative Computed Tomography (Pqct)mentioning
confidence: 99%
“…In the current study, LS was measured as an index of osteoblast number, and MAR was calculated as an index of osteoblast activity (35). As previously shown, 06/07/00 Endocrinology Page 10 the increase in LS was largely responsible for the PTH-induced increase in bone formation (29,33,34).…”
Section: Discussionmentioning
confidence: 66%
“…Studies performed in growing male (21,(32)(33)(34)(35) and female (36,37) rats demonstrated that chronic consumption of large doses of alcohol in the diet suppresses bone growth. The resulting relative osteopenia is due to the failure to acquire a normal bone mass and is relevant to juvenile alcohol abusers.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation